Deskripsi Sosial Ekonomi pada Film Tuhan Izinkan Aku Berdosa Sutradara Hanung Bramantyo Kajian Marxisme - Rosyta Aprilia Damatari; Andri Pitoyo; Marista Dwi Rahmayatis (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2026)
This study aims to examine the socio-economic aspect represented in the film "Tuhan Izinkan Aku Berdosa" directed by Hanung Bramantyo, through a Marxist perspective. The analysis focuses on the condition of the two main social clases, namely the proletariat and bourgeoisie, the relationship between these classes, and the prevailing economic system depicted in the film. The film is considered relevant for analysis using Marxist theory as it portrays social conflicts that reflect inequalities and power imbalances between social classes. Furthermore, the film not only presents an individual narrative with a relatively complex plot but also functions as a medium of social criticism toward injustices experienced by the lower class. This study employs a qualitative research method, with data obtained from the film’s narrative structure and dialogue. The data collection techniques used in this study include observation and documentation. The findings reveal the conditions of the proletariat and bourgeoisie classes, the dynamics of social class relations, the dominant economic system, and the implications of these aspects within the broader social context.